2022
DOI: 10.3390/pharmaceutics14061283
|View full text |Cite
|
Sign up to set email alerts
|

A Historical Review of Brain Drug Delivery

Abstract: The history of brain drug delivery is reviewed beginning with the first demonstration, in 1914, that a drug for syphilis, salvarsan, did not enter the brain, due to the presence of a blood–brain barrier (BBB). Owing to restricted transport across the BBB, FDA-approved drugs for the CNS have been generally limited to lipid-soluble small molecules. Drugs that do not cross the BBB can be re-engineered for transport on endogenous BBB carrier-mediated transport and receptor-mediated transport systems, which were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 1,176 publications
(2,041 reference statements)
1
119
0
Order By: Relevance
“…Using RMT to transport payload across the BBB has limitations, such as downregulating the targeted receptors and competition with natural ligands which may affect the receptors’ normal physiological functions [ 79 , 88 , 89 ]. For example, Couch et al, found that anti-TfR antibodies could cause a reduction of reticulocyte count and acute clinical signs [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using RMT to transport payload across the BBB has limitations, such as downregulating the targeted receptors and competition with natural ligands which may affect the receptors’ normal physiological functions [ 79 , 88 , 89 ]. For example, Couch et al, found that anti-TfR antibodies could cause a reduction of reticulocyte count and acute clinical signs [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of CNS manifestations in MPSs has been a critical but unmet need. However, a BBB-crossing technology based on the physiological mechanism of receptor-mediated transcytosis has been pioneered by Pardridge and colleagues [ 100 , 101 , 102 , 103 , 104 ] and paved the way for addressing this research gap. Recently, pabinafusp alfa, a BBB-penetrating fusion protein consisting of an anti-human transferrin receptor (TfR) antibody and IDS, was approved in Japan for the treatment of patients with all, including neuronopathic, forms of MPS II [ 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Therapies For Mpss Through the Reduction Of Gagsmentioning
confidence: 99%
“…The BBB proper consists of endothelial cells connected by tight junctions. The blood-CSF barrier is formed by choroid plexus epithelial cells also connected by tight junctions, but opposed to the BBB, the capillaries of the blood-CSF barrier are leaky, meaning that solutes of the plasma diffuse into the extracellular space of the choroid plexus where the epithelial cells selectively transport molecules to the CSF [2,3,14] From a quantitative drug delivery perspective, passaging across the BBB is by far the most important as the brain microvasculature has a surface area thousand-fold higher than that of the choroid plexus. This allow drugs to enter the entire brain while transport across the blood-CSF barrier is restricted to the ventricular system [2,3,15].…”
Section: Passaging Of Large Molecules Through the Blood-brain And Blo...mentioning
confidence: 99%
“…This includes entry via the paracellular space between the endothelial cells where tight junctions limit diffusion from blood to brain [1,2,9]. To enable nutrient uptake while preventing the influx of unwanted substances, the BECs express nutrient transporters for, e.g., amino-and fatty acids, monosaccharides, vitamins, and essential ions and metals [1][2][3][4]. In contrast, the transport of large molecules of the plasma, like albumin and IgG, is diminutive, e.g., intravenous injection of non-immune IgG in the adult rat is limited to as little as 0.03 % of the injected dose, which can be superseded more than ten-fold by injecting anti-rat transferrin receptortargeted IgG (OX26) [16].…”
Section: Passaging Of Large Molecules Through the Blood-brain And Blo...mentioning
confidence: 99%